Transcranial direct current stimulation as an ergogenic aid: a new perspective in sport - doi: 10.4025/reveducfis.v23i2.10670 - Marcelo Vitor-Costa; Lucas Adriano Pereira; Rafael Ayres Montenegro; Alexandre Hideki Okano; Leandro Ricardo Altimari (Revista da Educação Física)
The last two decades has followed an increase in interest from a large number of researchers interested in investigating the ergogenic potential of different resources that might assist in improving the physical performance of athletes in different sports. Most studies have focused on the mechanisms underlying the development of fatigue as this complex phenomenon is a limiting factor in sports performance. Thus, ergogenic resources that are effective in delaying the development of fatigue may improve athletic performance. Despite many discussions about fatigue, its exact cause is still a controversial subject. However, it has been suggested that cortical mechanisms may be involved and studies that have tried to modulate specific brain regions can provide valuable answers to better understand this phenomenon. Currently, (tDCS) has been used as a noninvasive tool that can modulate the excitability of specific regions of the cerebral cortex. Preliminary data have shown that tDCS anode is able to increase the excitability of motor cortex for up to one hour after its application and also increase the time until exhaustion in isometric exercise. These data suggest that tDCS can probably be used as a tool in research on mechanisms involved in the development of fatigue and perhaps as a potential ergogenic aid for athletes.